MANAJEMEN PEMBELAJARAN TAHFIDZ AL-QUR’AN DI PONDOK TAHFIDZ PUTRI ANAK-ANAK YANAABII’UL QUR’AN KARANGMALANG GEBOG KUDUS - Khamim Khamim; Barowi Barowi (PASCASARJANA UNISNU, 2018)
Abstract:This study is aimed to determine the implementation of learning tahfidz (memorizing) Al-Qur'an as well as supporting and inhibiting factors in the implementation of learning tahfidz Al-Qur'an at the Pondok Tahfidz Yanaabii'ul Qur'an for Children Gebog Kudus. This research was a field research using qualitative descriptive analysis techniques. Research data were obtained through interviews, observation and documentation. The collected research data were then analyzed using induction method and deduction method. From the results of data analysis, it can be concluded that; first, the implementation of the management of Islamic religious education learning at the Pondok Tahfidz Yanaabii'ul Qur'an for Children includes three stages, they are planning, implementation, and learning evaluation. planning has been carried out in accordance with process standards. The implementation of learning has also been carried out in accordance with the standard process, although in implementation there are still some lacks. The learning evaluation or assessment carried out by the Tahfidz teacher is also in accordance with the process standard. Second, the supporting factors in the management of tahfidz Al-Qur'an learning include; teachers as professional educators, the availability of learning media, the availability of adequate facilities and infrastructure, and the high interest in student learning. While the inhibiting factor in the management of learning tahfidz Al-Qur'an is the different of students’ ability.Keywords: Learning Management; Tahfidz al-Qur’an; Pondok Pesantren